Kangerdlugssuaq Glacier ice front positions, 1985-2018 - Bevan, Suzanne; Luckman, Adrian (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
Ice front positions for Kangerdlugssuaq Glacier based on digitisation of satellite images between 1985 to 2018. : The ice front of Kangerdlugssuaq Glacier was manually digitised on 733 satellite images acquired between April 1985 and November 2018. The satellite images include Landsat 5, Landsat 7, Landsat 8, ERS-1, ERS-2, Envisat Image Mode and Wideswath Mode, TerraSAR-X and Sentinel 1A and B Interferometric mode Ground Range Detected (IW GRD) images. The intersection points of the frontal vectors with 23 straight flow-parallel lines spaced at 160 m intervals were averaged to create mean ice-front positions. : The digitisation was carried out using Gamma Remote Sensing software module Polyras. : The accuracy of the data varies according to the initial spatial resolution and geolocation of the images and is likely to improve throughout the time sequence as processing and orbit vectors have improved. Bevan et al. (2012) estimated the accuracy for all types of imagery up to 2012 to be at least +/- 76 m.